O sistema de proteção social dos servidores públicos federais no Brasil: as políticas de previdência e saúde e a trajetória do serviço social, desde a assistência patronal até a GEAP - Fundação de Seguridade Social - Escorsim, Silvana Maria (2010)
The present thesis proposes rescuing the Brazilian constitution and the history course of the country protective policies, mainly referring to health and social security addressed to federal public employees. In this context, the present thesis sought to explain the Social Worker insertion into the Employers' Assistance created 1945 to provide health and social care to the Instituto de Aposentadorias e Pensões dos Industriários - IAPI (Industrial Worker Retirement and Pension Institute) until it was replace by: GEAP - Fundação de Seguridade Social (Social Security Foundation), privatized in 1990. This study is considered to be historical/institutional and restores the health policy, social security and supplementary health trajectories with their contradictions and unfolding derivate from different conjunctures, all based on the capitalist development model adopted by Brazil. In this thesis the Social Welfare Work was raised to a status of object of an investigation comprising a period from the time it was created up to the establishment of GEAP. Using the Oral History methodology as a reference, the held research performed semi-structured interviews with two professionals who worked for IAPI, IAPC and afterwards for INPS. It also analyzed questionnaires comprising structured and semi-structured questions designed by two groups of GEAP professionals: currently working and retired professionals. The research results showed the protective policy trajectory was permeated by the antagonism between two political projects: one was private-driven and the other was universal-driven - State. Today a dual-system is in effect. Also, there were changes in the attendance models that shaped the social welfare worker practices throughout the Historical/institutional trajectory. Nowadays, these practices comprise collective attendance processes developed under health and disease prevention programs and from the social rights perspective